2022
DOI: 10.3390/v14081738
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in a Mink Farm in Italy: Case Description, Molecular and Serological Diagnosis by Comparing Different Tests

Abstract: This study described a SARS-CoV-2 infection in minks on an Italian farm. Surveillance was performed based on clinical examination and a collection of 1879 swabs and 74 sera from dead and live animals. The farm was placed under surveillance for 4.5 months, from the end of July 2020, when a man working on the farm tested positive by RT-PCR, till mid-December 2020 when all the animals were sacrificed. Clinical examination revealed no clinical signs or increased mortality rates attributable to SARS-CoV-2, while di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This is particularly important given that outbreaks may not be associated with any clinical signs or increased mortality in infected mink. 2,24 We found that there was a small but significant difference between RT-rtPCR assays targeting the SARS-CoV-2 E versus RdRp gene. Both assays were clearly capable of detecting the 3 different strains of virus circulating on the 3 infected farms and in different sample types.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This is particularly important given that outbreaks may not be associated with any clinical signs or increased mortality in infected mink. 2,24 We found that there was a small but significant difference between RT-rtPCR assays targeting the SARS-CoV-2 E versus RdRp gene. Both assays were clearly capable of detecting the 3 different strains of virus circulating on the 3 infected farms and in different sample types.…”
Section: Discussionmentioning
confidence: 88%
“…The clinical presentation and epidemiology of these outbreaks have been somewhat variable. In some, infection of mink on affected farms has occurred in the absence of visible disease 2,24 ; in other cases, there has been increased mortality as well as clinical signs including reduced feed intake, nasal discharge, respiratory distress, and diarrhea. 4,23,33 Postmortem examinations of naturally and experimentally infected mink have indicated that SARS-CoV-2 primarily affects the respiratory tract causing rhinitis and interstitial pneumonia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In certain cases, human-to-animal transmission led to onward epizootic circulation of SARS-CoV-2, as in the case of farmed American minks reported from many European and American Countries ( 39 , 54 56 ), and of white-tailed deer ( Odocoileus virginianus ) in North America ( 11 , 12 ) ( Figure 1 ). Transmission within animal populations may promote the origin of new variants as a consequence of evolutionary changes in the virus.…”
Section: Surveillance In Wildlifementioning
confidence: 99%